2012
DOI: 10.1074/jbc.m112.365049
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Oxytocin Mediates the Anabolic Action of Estrogen on the Skeleton

Abstract: Background:The mechanism underlying the anabolic effect of estrogen on the skeleton is unclear. Results: We report that estrogen-induced bone formation in mice occurs through oxytocin (OT) produced by osteoblasts in bone marrow. Conclusion: Feed-forward OT release in bone marrow by a rising estrogen level may facilitate rapid skeletal recovery after lactation. Significance: The study highlights a novel mechanism for estrogen action on bone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
78
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(82 citation statements)
references
References 34 publications
4
78
0
Order By: Relevance
“…Primary BMSCs were performed using bone marrow from mouse femurs and tibia as previously described (63 Osteoclast cultures were performed as described previously (64). Briefly, bone marrow hematopoietic cells were plated in the presence of macrophage colony-stimulating factor (MCSF) (30 ng/ml) for 2 d, followed with both MCSF and receptor activator of nuclear factor kappa-B ligand (Rankl) (25 ng/ml) for 3-5 d. Osteoclast cultures were fixed in 3.7% (vol/vol) formaldehyde and 0.1% Triton X-100 for 5 min, and stained for Trap.…”
Section: Discussionmentioning
confidence: 99%
“…Primary BMSCs were performed using bone marrow from mouse femurs and tibia as previously described (63 Osteoclast cultures were performed as described previously (64). Briefly, bone marrow hematopoietic cells were plated in the presence of macrophage colony-stimulating factor (MCSF) (30 ng/ml) for 2 d, followed with both MCSF and receptor activator of nuclear factor kappa-B ligand (Rankl) (25 ng/ml) for 3-5 d. Osteoclast cultures were fixed in 3.7% (vol/vol) formaldehyde and 0.1% Triton X-100 for 5 min, and stained for Trap.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, to examine potential antianabolic actions of Oxt via the Avpr1α, we used a murine lactation model of bone loss in which the Oxtr was deleted specifically in osteoblasts (10,34). Mice lose bone maximally at weeks 2 and 3 of lactation, after which there is prompt skeletal recovery at weaning.…”
Section: Discussionmentioning
confidence: 99%
“…We find high levels of Oxtr expression on both osteoclasts and osteoblasts (2,10), in addition to their abundant expression in breast and uterine tissue, where they regulate lactation and parturition, respectively (11). Avpr1αs, in contrast, are distributed more ubiquitously, whereas Avpr2s are localized mainly in the kidney, where they regulate free water excretion (12).…”
mentioning
confidence: 92%
“…More recently, we and others have shown that Oxt also stimulates bone formation directly by interacting with an osteoblastic Oxtr (3,4). The genetic deletion of Oxt or Oxtr in mice thus decreases osteoblast differentiation and bone formation, causing osteopenia (5,6). We believe that this action supports maternal skeletal remineralization after the intergenerational transfer of calcium during pregnancy and lactation (5).…”
mentioning
confidence: 66%
“…We have shown previously that osteoblasts express abundant plasma membrane Oxtrs that drive cell differentiation to a mature, mineralizing phenotype in response to pituitary-and bone marrow-derived Oxt (4,6). However, the mechanism of this effect has remained uncertain.…”
Section: Discussionmentioning
confidence: 99%